Flooding and loading in packed columns absorption (Research, Society and Development, 2021)
In the present work, the hydrodynamics of an absorption tower with filling of glass rings is studied through the determination of the flooding and loading ranges in the absorber operation. In the flooding, the gas phase prevents the flow of the liquid stream, causing it to drag along the top of the column. In the study, various combinations of flow rates are tested and the loading and flooding points. Three operating regions are determined and the critical point of operation, where the pressure difference in the column stabilizes is also obtained.